Bovine herpesvirus 1 regulatory proteins are detected in trigeminal ganglionic neurons during the early stages of stress-induced escape from latency - Insun Kook; Alan Doster; Clinton Jones (Journal of NeuroVirology, 2015)

Large effects of consumer offense on ecosystem structure and function - Michael F. Chislock; Orlando Sarnelle; Brianna K. Olsen; Enrique Doster; Alan E. Wilson (Ecology, 2013)
Study of the role of within‐species adaptation in ecological dynamics has focused largely on prey adaptations that reduce consumption risk (prey defense). Few, if any, studies have examined how consumer adaptations to overcome prey defenses (consumer offense) affect ecosystem structure and function. We manipulated two sets of genotypes of a planktonic herbivore ( Daphnia pulicaria ) in a highly productive ecosystem with abundant toxic prey (cyanobacteria). The two sets of consumer genotypes varied widely in their tolerance of toxic cyanobacteria in the diet (i.e., sensitive vs. tolerant). We found a large effect of tolerant D. pulicaria on phytoplankton biomass and gross primary productivity but no effect of sensitive genotypes, this result stemming from genotype‐specific differences in population growth in the presence of toxic prey. The former effect was as large as effects seen in previous Daphnia manipulations at similar productivity levels. Thus, we demonstrated that the effect of consumer genotypes with contrasting offensive adaptations was as large as the effect of consumer presence/absence.

A protein encoded by the bovine herpesvirus 1 open reading frame E gene induces neurite-like morphological changes in mouse neuroblastoma cells and is expressed in trigeminal ganglionic neurons - Sandra Perez; Florencia Meyer; Gail Henderson; Yunquan Jiang; Simon Sherman; Alan Doster; Melissa Inman; Clinton Jones (Journal of NeuroVirology, 2007)

Comparison of inflammatory infiltrates in trigeminal ganglia of cattle infected with wild-type Bovine herpesvirus 1 versus a virus strain containing a mutation in the LR (latency-related) gene - Sandra Perez; Luciane Lovato; Joe Zhou; Alan Doster; Clinton Jones (Journal of NeuroVirology, 2006)